State Youth Policy In New Uzbekistan - Mavlonov Kamoliddin Boborakhmatovich; Ergasheva Yulduz Alimovna (Zien Journals, 2025)
This scientific article analyzes the effectiveness of the youth work system in the Republic of Uzbekistan. The article discusses the main directions of youth policy, legal and regulatory documents aimed at supporting young people socially, economically, and culturally, as well as opportunities created for their active participation in society. The article is focused on examining the development of youth, supporting their activities, and the policies implemented in this regard
Keywords: Youth policy; legal and regulatory documents; the role of youth in society